Variations in Observations of Geosynchronous Magnetopause and Last Closed Drift Shell Crossings With Magnetic Local Time - Thomas A. Daggitt; Richard B. Horne; Sarah A. Glauert; Giulio DelZanna; Mervyn P. Freeman (Space Weather)
Abstract We analyze a set of events in which both electron flux dropouts caused by magnetopause shadowing and geosynchronous magnetopause crossings (GMCs) are observed. These observations are compared to event‐specific last closed drift shell (LCDS) models derived from the TS05 and TS07 external field models and magnetopause standoff distance. The LCDS models show good association with losses due to magnetopause shadowing but fail to reproduce observations of GMCs on the timescale of minutes. We show that different satellites in geostationary orbit observe different trends in electron flux during storm events on timescales of less than a day due to their separation in longitude. These differences demonstrate that both satellite L* and magnetic local time must be taken into account when modeling rapid variations in the outer radiation belt, and at least three satellites in geostationary orbit, ideally more, may be required for accurate forecasting and reconstruction of these events on timescales shorter than days.